2015
DOI: 10.1021/acs.biochem.5b00801
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of Tetratricopeptide Repeat Proteins to Heat Shock Protein 70 (Hsp70) and Heat Shock Protein 90 (Hsp90) Is Regulated by Affinity and Phosphorylation

Abstract: The heat shock proteins Hsp70 and Hsp90 require the help of tetratricopeptide repeat (TPR) domain-containing co-chaperones for many of their functions. Each monomer of Hsp70 or Hsp90 can only interact with a single TPR co-chaperone at a time and each member of the TPR co-chaperone family brings distinct functions into the complex. Thus, competition for TPR binding sites on Hsp70 and Hsp90 appears to shape chaperone activity. Recent structural and biophysical efforts have improved our understanding of chaperone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 68 publications
5
82
0
Order By: Relevance
“…The binding exhibits various degrees of specificity between the two partners; Hsp90, for example, is preferred over Hsp70 to bind to the TPRs of the large FKBPs (Assimon et al 2015;Guy et al 2015). In particular, peptide-TPR co-crystal structure and mutational analysis have established that the invariant C-terminal pentapeptide, MEEVD, of Hsp90 (Gupta 1995) interacts with specific residues that are common to the TPRs of long FKBPs and CYNs (Assimon et al 2015;Cliff et al 2006;Scheufler et al 2000;Ward et al 2002;Wu et al 2004). The residues, found to be absolutely essential for MEEVD binding, are: K5, N9 in TPR1, N6 in TPR2, and K2, R6 in TPR3.…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…The binding exhibits various degrees of specificity between the two partners; Hsp90, for example, is preferred over Hsp70 to bind to the TPRs of the large FKBPs (Assimon et al 2015;Guy et al 2015). In particular, peptide-TPR co-crystal structure and mutational analysis have established that the invariant C-terminal pentapeptide, MEEVD, of Hsp90 (Gupta 1995) interacts with specific residues that are common to the TPRs of long FKBPs and CYNs (Assimon et al 2015;Cliff et al 2006;Scheufler et al 2000;Ward et al 2002;Wu et al 2004). The residues, found to be absolutely essential for MEEVD binding, are: K5, N9 in TPR1, N6 in TPR2, and K2, R6 in TPR3.…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…Fluorescence polarization assay: Fluorescence polarization (FP) studies were carried out as previously described (Assimon et al, 2015). Briefly, the FP tracer was composed of a peptide derived from Hsp72/HSPA1A (GSGPTIEEVD) that was coupled at the N-terminus Products were visualized using a Bio-Rad ChemiDoc XRS+ imaging system and quantified using ImageJ software.…”
Section: Experimental Assays Involving Chipmentioning
confidence: 99%
“…Given that T636 phosphorylation seems especially prevalent in proliferating cancer cells, this could be a prime determinant of oncoprotein stability, driving cancer cell growth (11). More recent studies have shown that T636 phosphorylation, while greatly impacting HOP and CHIP interactions had little effect on the binding of other co-chaperones such as DnaJC7, FKBP51 and FKBP52, even though they bind to Hsp70 at roughly the same location (12). The regulation of the selectivity of binding to co-chaperones remains obscure, but an interesting facet of chaperone quality control.…”
Section: Regulation Of Hsp70 Client Triaging By Phosphorylationmentioning
confidence: 99%